Impact of Body Weight, Height, and Obesity on Selection of Skin Entry Point for Transforaminal Endoscopic Lumbar Discectomy - Patgaonkar, Prasad; Goyal, Vaibhav; Agrawal, Utkarsh; Marathe, Nandan; Patel, Vivek (Asian Journal of Neurosurgery, 2022)
Background Prospective evaluation of the effect of physical parameters like height, weight and abdominal girth on different skin entry points in transforaminal endoscopic lumbar discectomy (TELD) in lower lumbar discs.Methods This prospective study involved 174 patients with unilateral radicular pain or discogenic back pain, central, paracentral disc herniations and lateral canal stenosis at the level from L3 to S1 radiologically confirmed by magnetic resonance imaging (MRI) and failed conservative trial for 6 weeks. All patients underwent measurements of height, weight, body mass index (BMI), and abdominal girth preoperatively. All the four possible entry points, i.e., 45 to 45, posterolateral (PL), tip of spinous process (TOSP), and dorsum of the facet joint, were marked and point midway between PL and TOSP (PL-TOSP) skin entry was used.Results The change in the value, i.e., distance from midline of all the entry points with physical parameters like height, weight, BMI, and abdominal circumference was statistically significant. The visual analog scale score decreased from a preoperative value of 7.98 to 1.84 at 6 months follow-up. The Oswestry disability index score improved from 72.53 to 16.26.Conclusion The entry point in TELD is not a fixed value as it varies with the physical parameters like weight and abdominal girth of the patient. PL-TOSP is a safe entry point for common pathologies like central, paracentral herniations and lateral canal stenosis in lower lumbar levels and can be predicted preoperatively by proposed formula.
Keywords: TELD; PL-TOSP; lumbar disc herniation; endoscopy